Doses of inoculant and nitrogen at sowing of soybean in first cultivation area Doses de inoculante e nitrogênio na semeadura da soja em área de primeiro cultivo - da Silva A.F. (2011)
The inoculation of soybean crop with Bradyrhizobium bacteria is a widespread practice, due to excellent results achieved in productivity, however, some doubt still arise in relation the need of application of mineral nitrogen at sowing. In that mean, this work aimed to evaluate the response of the doses at inoculant and mineral nitrogen in the sowing of crop soybean in area of first cultivation. The experiments were carried in the experimental field of the University of the Estate of Mato Grosso, Campus of Alta Floresta - MT, Brazil, in the growing seasons of 2006/2007 and 2007/2008. The experimental design was randomized blocks, in a factorial escheme 2 × 4, with four replications. The factors consisted in the inoculation of seeds with Bradyrhizobium japonicum (3 e 6 mL kg -1 of seeds), and nitrogen fertilizer at sowing (0, 10, 20 e 40 kg ha -1). The following variables were evaluated: plant height, insertion height of first pod, number of pod per plant, number of grain per pod, mass of 100 grain and grain productivity. In the two growing seasons there was no significant difference for doses of inoculants applied in first year of cultivation with soybean. To nitrogen application at sowing of soybean crop there was quadratic effect to plant height and of insertion height of first pod and growing linear to number of pod per plant in the second year of cultivation, however, without significant increase the productivity.